Studies on blocking of replicase of human corona virus by bioactive compounds-In silico and Molecular Docking Studies - Lahiri, Dibyajit; Nag, Moupriya; Dash, Sudipta; Dutta, Bandita; Ray, Rina Rani (International Journal of Scientific Research in Biological Sciences, 2020)
The sudden outbreak of COVID-19 as pandemic affected people at large and resulted in a high mortality rate throughout the world. Although according to WHO, more than 200 drugs are under the process of clinical trials, till date no proper medication is available for treating this pandemic. The present work was an attempt to provide information about the bioactive ingredients being present within the indigenous plants that can be used as a potential drug against SARS-CoVs since they show considerable interaction with the viral replicating protein; replicase 6W4B (PDB). It was observed the Quercetin and Curcumin had remarkable interaction with the target protein and had a binding energy of -52.273Kcal/mole and -43.909 Kcal/mole respectively that were comparatively higher than hydroxychloroquine. Both of the bioactive compounds possessed same docking site and interacted with GLNA 50 by a hydrogen bond, like that of hydroxychloroquine, a widely used remedial drug against COVID 19. This research may help in providing an alternative idea on drug development from the easily available indigenous plants for combating against COVID-19.